Correlation of ASA Physical Status With The Achievement of Bromage Score In Post Subarachnoid Block Anesthesia Patients - Artika, Regita Cahya; Riyadi, Raden Sugeng; Dewi, Ratih Kusuma (Poltekkes Kemenkes Aceh, 2025)
Background: After surgery with subarachnoid block anesthesia, patients need to be closely observed, one of which is by monitoring the motor function of the lower extremities using the Bromage Score parameter. The length of motor recovery time is an important indicator because recovery that is too long can increase the risk of complications, such as paresthesia, which ultimately leads to an extension of the patient's treatment period. The time to achieve a normal Bromage Score is influenced by various factors, one of which is the patient's physical status which is classified through the American Society of Anesthesiologists (ASA) assessment. Accurate ASA physical status assessment is very important because it can help predict the risk of anesthesia, estimate the duration of recovery, and minimize the occurrence of serious complications that have the potential to threaten patient safety. Purpose: To determine the correlation between ASA physical status and the achievement of Bromage score ≤ 2 in post-subarachnoid block anesthesia patients at PKU Muhammadiyah Hospital, Yogyakarta. Methods: This study is a quantitative study with a correlation analytical approach. The population taken were patients who would undergo surgery with subarachnoid block anesthesia using a saturated sampling technique with a sample size of 76 respondents. The research instrument used a physical status observation sheet according to ASA standards and an observation sheet for achieving a Bromage score ≤ 2 and a watch to calculate the achievement time. Results: Based on statistical analysis using the Spearman's Rho test, a 2-tailed sig value of 0.000 < 0.05 was obtained, which means that there is a correlation between ASA physical status and the achievement of a Bromage score ≤ 2 in patients after subarachnoid block anesthesia. Conclusion: There is a correlation between ASA physical status and the achievement of Bromage score ≤ 2 in patients after subarachnoid block anesthesia at PKU Muhammadiyah Hospital Yogyakarta with a very strong level of relationship and a positive direction of correlation.